The Risky-Opportunity Analysis Method (ROAM) to support risk-based decisions in a case-study of critical infrastructure digitization - Ali Aghazadeh Ardebili; Elio Padoano; Antonella Longo; Antonio Ficarella (Risks, 2022)
Socio-ecologic, socio-economic, and socio-technical transitions are opportunities that require fundamental changes in the system. These will encounter matters associated with security, service adoption by end-users, infrastructure and availability. The purpose of this study is to examine and overcome the risks to take advantage of opportunities through the novel Risky-Opportunity Analysis Method (ROAM). A novel quantitative method is designed to determine when, after making some changes, the risks become acceptable so that the opportunity does not deviate from the objectives. The approach provided a quantitative evaluation of the possible changes in parallel with digitization, towards providing a green Service Supply Chain (SSC). The result of ROAM shows that the most cost-effective change to increase the resilience of the system is a solution (SMS) which is different from that identified by a TOPSIS multi-criteria method. Real-word decisions in change management should tackle the complexity of systems and uncertainty of events during and after transition through a careful analysis of the alternatives. A case-study was carried out to evaluate the alternatives of an ancillary service in the Payment Service Providers (PSP). The comparison of the ROAM results with the traditional TOPSIS of the case-study unveils the priority of the ROAM in practice when the alternatives are Risky-Opportunities. The existing risk assessment tools do not take advantage of risky opportunities. To this aim, the current article introduces the term Risky-Opportunity, and two indexes - Stress and Strain - of the alternatives that are designed to be employed in the new quantitative ROAM approach.
Keywords: 330; change management; critical infrastructure resilience; cyber-physical-social systems; digitization; payment service providers (PSP); risk management; risky-opportunity (RO); risky-opportunity analysis method (ROAM); socio-ecological transition